Stability of Silk Fibroin Blend Films with Silk I Structure (Journal of Fiber Bioengineering and Informatics, 2021)
The crystalline structure of silk fibroin Silk I is generally considered to be metastable structure and will transition to the crystalline structure of Silk II, however, under what conditions this crystalline structure is stable and under what conditions the transition will occur is not definite. In this paper, silk fibroin protein solution was prepared from silkworm cocoon, the glycerol/silk fibroin protein blend film containing Silk I crystalline structure was prepared with a glycerol/silk fibroin mass ratio of 20: 100, and a pure silk fibroin solution was used as a raw material to prepare a silk fibroin protein film rich in random coil structure. Different concentrations of methanol and ethanol were used to soak the above two materials to investigate the influence of monohydric alcohol on the crystalline structure of silk fibroin materials. X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), Raman scattering spectroscopy (Raman) and Thermogravimetric analysis (TGA) were used to characterize the structure of silk fibroin before and after the treatments. The results showed that after methanol and ethanol treatment, the pure silk fibroin protein film with random curled structure was transformed into Silk II crystal structure, while the glycerin/silk fibroin protein film still showed the crystal structure of Silk I without obvious transformation. Two experimental methods of high temperature wetting and high temperature soaking were set, and four temperature gradients of 60°C, 80°C, 100°C and 120°C were set to explore the influence of high temperature on the structure of silk fibroin protein materials. In order to investigate the time stability of crystal structure of Silk I, glycerin/silk fibroin blend film and pure silk fibroin protein film were placed in an oven at 60°C for 32 days. The structure of the material was examined by XRD, FTIR and Raman test techniques before and after placement. The results showed that the glycerin/silk fibroin film with crystal structure of Silk I had no obvious structural changes and had good humidity and heat stability and time stability. The random coil structure of pure Silk film gradually changed to the more regular crystal structure of Silk I and Silk II. Glycerin/silk fibroin protein blend film has considerable stability and can be used as biomaterials.